The effects of age on cerebral activations: internally versus externally driven processes - Hu, Sien; Chao, Herta H.; Winkler, Alissa D.; Li, Chiang-shan R. (Frontiers in Aging Neuroscience, 2012)
Numerous studies using functional magnetic resonance imaging (fMRI) have described increased or decreased regional brain activations in older as compared to younger adults. This seeming inconsistency may reflect differences in the psychological constructs examined across studies. We hypothesized that behavioral tasks/contrasts engaging internally and externally driven processes are each associated with age-related decreases and increases, respectively, in cerebral activations. We examined the fMRI data of 103 healthy adults, 18 to 72 years of age, performing a stop signal task (SST), in which a frequent ‘go’ signal triggered a prepotent response and a less frequent ‘stop’ signal prompted inhibition of this response. Greater internally driven processes lead to stop successes (SS) as compared to stop errors (SE), and to speeding up instead of slowing down in go trials. Conversely, externally driven processes contribute to SE trials, which resulted from habitual, unmonitored responses triggered by the go signal (as compared to SS trials), and involved perceptual and cognitive processes elicited by the stop signal (as compared to go trials). Consistent with our hypothesis, the results showed age-related decreases and increases in cerebral activations each during these respective internally and externally driven processes. These findings further elucidate the influence of age on cognitive functioning and provide an additional perspective to understand the imaging literature of aging.